Deleuze and contemporary art - Zepke, Stephen; O'Sullivan, Simon 1967- (Edinburgh University Press, 2010)
Leading figures in the Deleuzean philosophy of art criticism field contribute chapters that explore the extensive writings on art art history and aesthetics in the realm of contemporary art of Deleuze and Guattari